DETERMINATION OF PARAMETERS OF THE TUBBING RINGS OF THE TUNNEL - Borisov, Ye. O. (Science and Transport Progress, 2007)
The article proposes a method of finding spatial position of tubing rings on the basis of linearly-angular measurings of a larger number of points in two mutually perpendicular planes. After processing of measuring results, data are obtained about displacement of center and points of ring in relation to the initial (projected) values.